PERFORMANCE FORM ANALYSIS AND SYMBOLIC MEANING OF UBARAMPE JARAN KEPANG ART TURANGGA SAKTI SEMAWUNG VILLAGE PURWOREJO DISTRICT PURWOREJO REGENCY - Arifin Septiyanto; Aris Aryanto; Eko Santosa (Jurnal Ilmu Bahasa, Sastra dan Pengajarannya, 2026)
This research is motivated by the enduring existence of jaran kepang traditional art, which remains popular as a form of entertainment among the people of Purworejo and continues to develop in line with changing times. Although numerous studies on jaran kepang have been conducted, research specifically examining the performance structure, the symbolic meaning of ubarampe (ritual offerings), and the functions of the Turangga Sakti group in Semawung Village, Purworejo District, Purworejo Regency, is still limited. Therefore, this study aims to describe: (1) the performance form of the Turangga Sakti jaran kepang in Semawung Village, (2) the symbolic meaning of ubarampe in the performance, and (3) the functions of the Turangga Sakti jaran kepang art. This study employs a qualitative approach with a descriptive method. Data collection techniques include observation, interviews, and documentation. The research informants consist of the chairman, vice chairman, and senior members of the art group. Data analysis is conducted using descriptive qualitative techniques, while data validity is tested through triangulation. The results show that the jaran kepang performance of Turangga Sakti in Semawung Village consists of interconnected elements, including history, performers, shamans (pawang), singers (wiraswara and waranggana), performance time and place, musical instruments, makeup, costumes, dancer properties, and ubarampe or ritual offerings. These elements are harmoniously integrated, producing a structured and cohesive performance. The symbolic meaning of each ubarampe represents an expression of human gratitude to God Almighty. Furthermore, the functions of this art include a medium for self-expression, entertainment, education, cultural preservation, and community economic support.